1998
DOI: 10.1017/s0952523898155049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the postnatal growth of visual cortex

Abstract: Development and growth of V1 begins during embryogenesis and continues postnatally. The growth of V1 has direct implications on the organization of features such as the retinotopic map and the pattern of visual cortical columns. We have examined the postnatal growth and two-dimensional shape of V1 in macaque monkeys, cats, and rats. The perimeter, area, and anterior-posterior length of V1 were measured from unfolded and flattened sections from neonatal and adult animals from each of these species. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
(45 reference statements)
4
28
1
Order By: Relevance
“…for fixed R. On the basis of the experimental work of Duffy et al (1998), who showed that between postnatal weeks 3 and 6 cat V1 undergoes a uniform expansion in which it approximately doubles in size, we assume that the growth is slow and isotropic. It should be noted that our extension of the Swindale model is formulated in terms of the normalized synaptic density n = (n L − n R )/N where N = n L + n R is the fixed total density at each point in cortex.…”
Section: Developmental Model On a Growing Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…for fixed R. On the basis of the experimental work of Duffy et al (1998), who showed that between postnatal weeks 3 and 6 cat V1 undergoes a uniform expansion in which it approximately doubles in size, we assume that the growth is slow and isotropic. It should be noted that our extension of the Swindale model is formulated in terms of the normalized synaptic density n = (n L − n R )/N where N = n L + n R is the fixed total density at each point in cortex.…”
Section: Developmental Model On a Growing Domainmentioning
confidence: 99%
“…In the case of cats (and ferrets), ocular dominance columns can be visualized at a very early postnatal stage (Crowley and Katz, 2000;Crair et al, 2001), during which the cortex is still undergoing significant growth. Indeed, Duffy et al (1998) have shown that the surface area of adult cat V1 is more than double that of 1-week-old kittens, with the shape of V1 remaining unaltered. Although ocular dominance columns in macaque are fully formed at birth, the macaque brain undergoes a much smaller degree of postnatal growth (around 16%) (Purves and LaMantia, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…In cat, the neocortical volume increases from ≈1000mm 3 at birth to ≈4500mm 3 in adulthood [2]. Consistently, the surface area of cat primary visual cortex (V1) increases postnatally by a factor of 2.5 between week 1 and week 12 [3]. This size increase implies that the distance between any two neuronal cell bodies grows on average by a factor of 1.6 during postnatal development.…”
Section: Introductionmentioning
confidence: 95%
“…Only a few studies describe differences in the size, shape and locations of cortical areas across a population of individuals. Differences have been described in the size and shape of primary visual cortex in humans, macaques, cats, rats and mice, the consensus being that V1 differs in size more than in shape (Van Essen, Newsome & Maunsell, 1984;Duffy, Murphy & Jones, 1998;Hinds et al, 2008;Garrett et al, 2014). Necessarily, comparisons were across small numbers (<25) of individuals and no attempt was made to determine whether the differences resulted from differing organization of cortex across individuals (biological variation) or simply measurement error (noise).…”
Section: Introductionmentioning
confidence: 99%